HIGH TREASON IN THE CRIMINALL LEGISLATION OF THE REPUBLIC OF SERBIA - Matić, Goran (The Policy of National Security, 2024)
The beginning of the 21st century has brought about a large number of security and political problems at the regional and global levels, ranging from the unilateral recognition of the so-called “Kosovo”, military intervention in Ukraine, Israel’s military intervention in Gaza Strip, a number of armed conflicts on the African soil to the radicalisation of the problem in the relations between China and Taiwan. In addition, the disintegration of the Socialist Federal Republic of Yugoslavia (SFRY) was preceded by a large number of activities directed at destroying the constitutional order and security of the SFRY as well as of the Federal Republic of Yugoslavia, the impacts of which are felt in the Republic of Serbia to this date. It is for that reason that this paper sets out some legal aspects of high treason in terms of attacking the constitutional order and security, and calling for a violent change of the constitutional order of the Republic of Serbia, as one of the forms of repressive activities and criminal legal protection of the constitutional order and security, or protection of the existence of the state itself, which is an equally important legal issue in the 20th and 21st century alike. It should be noted that the treatment of the problem area of high treason has been neglected in both theory and practice. Thus this paper gives a review of historical development of legal aspects of high treason through the prism of protecting the constitutional order of Serbia. Within the critical examination of the current legislation, the paper provides a detailed analysis of the provisions of Article 308. (Attack against the Constitutional Order) and Article 309. (Calling for a Violent Change of the Constitutional Order) of the Criminal Code of the Republic of Serbia; the same applies to the necessary extent to the provisions of Article 319. (Conspiracy against the Constitutional Activity), Article 320. (Preparation of acts against the Constitutional Order and Security of Serbia) and Article 321. (Serious Offences against the Constitutional Order and Security of Serbia). The paper also points to some interesting solutions we find in the comparative law.